Kinerja Perusahaan Terkait dengan Teknologi Informasi, Lingkungan dan Kompetensi - Eko Purwanto; M.S. Idrus; Kusuma Ratnawati; Made Sudarma (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
Whether in the organization’s manufacturing companies in Indonesia, implementation of the applied information technology has an impact, either directly or indirectly, to the performance. The population of this research were companies listed at the Dinas Perindustrian dan Perdagangan Wilayah Jawa Timur, and implementing information and communication technology on a local area network. Units analysis were 117 manufacturing companies that employs 500 employees or more, implementing information and communication technology on a local area network, and represented by leader or information technology manager as respondent. All data were analyzed with Structural Equation Modeling (SEM) using the SPSS AMOS 16. The insignificant hypotheses suggests that the higher level of the ICT system completeness, the higher performance achievement of the corporate organization. The other two indirect influence hypothesis that suggest significant relationships through conduciveness organizational environment and personnel competences are proven strictly. The result of this research shows that the ICT system completeness may only influence the performance of corporate organization when the system is able to improve the conduciveness organizational environment and increase the personnel competences on the decision making process.Keywords: Information Technology, Organizational Environment, Competence, IT Scorecard, Balanced Scorecard, dan Organization Performance.